PERENCANAAN PENDIDIKAN PERSPEKTIF MASYARAKAT PEDESAAN DI KABUPATEN LAHAT - Kanada, Rabial (Universitas Nurul Jadid, 2020)
This study aims to describe the concept of educational planning for rural communities in Lahat district. This research is a qualitative qualitative research. Research subjects are rural people who will, are, and after sending their children to school. The data technique uses observation, interviews, and documentation. The data analysis technique was carried out in stages, namely data reduction, data presentation, and data collection. To maintain the validity of the data in the presentation, analysis was carried out with triangulation of sources and techniques. The results showed that there are 4 important elements in educational planning in rural communities, namely the choice of place and department, children's academic ability, parents' financial ability, educational goals, and study time. These four elements influence each other in rural community education planning.